2012
DOI: 10.5424/sjar/2012102-447-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of PCR-sexing procedures using bovine embryos fertilized with sex-sorted spermatozoa

Abstract: Sex determination in bovine embryos is a useful tool in reproductive biotechnology. This work compares two techniques of embryo sexing by polymerase chain reaction (PCR). Embryos were produced in vitro with sex-sorted sperm and two techniques of DNA lysis were tested (proteinase K versus heat shock). Subsequently, halves of each lysed sample was amplified both by amelogenin and BRY4a/SAT1 primers. Male embryos treated by both digestion methods and amplified by BRY4a/SAT1 gave higher rates of false negatives. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Our sexing method [33] consists of an accurate built-in control PCR, which is particularly appropriate when an accurate embryonic sex diagnosis is necessary [64]. Commercially available, sex-sorted sperm usually allow embryos of the desired sex at rates of 90% or higher, which has been confirmed by PCR in the present work.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our sexing method [33] consists of an accurate built-in control PCR, which is particularly appropriate when an accurate embryonic sex diagnosis is necessary [64]. Commercially available, sex-sorted sperm usually allow embryos of the desired sex at rates of 90% or higher, which has been confirmed by PCR in the present work.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, the use of Vero cells shows an embryotrophic effect by producing growth factors and also removing toxicants or inhibitory substances derived from the embryo [59]. However, in a previous work [33] we demonstrated that embryos produced without serum had better survival and hatching rates after vitrification (open pulled straw), pointing toward different qualities among the embryos. To our knowledge, there are no data about how culture systems might improve the diminished developmental ability of embryos produced with sexed sperm, and we hypothesize that in our case the developmental ability of the embryos fertilized with sexed sperm does not depend on the culture system, but on the bull and the damage inflicted to the sperm by the sorting process.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…6 Embryos were in vitro produced (IVP) with frozen male or female sex-sorted sperm (Sexing Technologies; Navasota, TX, USA) as previously reported. 31 Early morulae were transferred to the ipsilateral horn of estrus-synchronized, cross-bred beef heifers on day 5 after in vitro fertilization (IVF) and were recovered on day 8 (see below) or sustained in vitro up to day 8.…”
Section: Animals and Embryosmentioning
confidence: 99%